La défiance envers la médecine - une injustice épistémique envers les médecins ou envers les patient·es ? - Marie-Lou Reymondon (Éducation et Socialisation)
This article seeks to prevent the concept of testimonial injustice from being used extensively and abusively to characterize patients' distrust of doctors. By emphasizing the concept of social prejudice at the core of the definition of testimonial injustice, it would appear wiser to restrict the use of this term to cases where this mistrust is linked to the doctor's real or supposed belonging to a stigmatized social category, rather than extending it to all situations of mistrust towards the medical institution. How can other situations of patient mistrust be explained ? Many of these situations can be interpreted as cases of epistemic injustice suffered by patients themselves - and more precisely, hermeneutical injustice or epistemic trust injustice. Patients are the first to suffer because of this mistrust, and the medical institution has a responsibility in perpetuating it, especially when it concerns stigmatized groups who have suffered medical violence. It is therefore necessary to understand the credibility granted to doctors on the basis of the patients' social context and situation, in order to reveal cases where patients' mistrust may be justified and rational, while being potentially harmful for their health.